Participación en pasantía internacional para la modificación básica, desarrollo de ejecución y estructura en proyectos de arquitectura (2018)
The work methodology that comprises the Gestión 360​​° company links the client as the main piece that encourages the participation of all the areas of work of the same, seeking as an objective to satisfy the needs of the client without neglecting the delicate rule that governs the processes of renewal and urban intervention.